Seed waste of mango (Mangifera indica) as raw material glucose syrup alternative substitute for synthetic sweetener - Taufik Abdullah; Nurhidayatullah Nurhidayatullah; Bidarita Widiati (Jurnal Pijar Mipa, 2022)
The search for alternative ingredients as natural sweeteners needs to be done. The sweeteners circulating in the market are synthetic sweeteners with no nutritional value and harm health. This research aims to produce a safe sweetener in the form of glucose syrup, which can be used as an alternative to artificial sweeteners through enzymatic reactions, and to find out the suitable reaction conditions to produce glucose syrup with the highest levels in several combinations of pH and temperature. Mango seed core is a source of carbohydrates that can be used as glucose syrup. The average starch content of 1940.1 grams of wet mango core is 10.09%. The starch was hydrolyzed with alpha-amylase and glucoamylase. It is biocatalysts through liquefaction stages (pH 5 and 6) and saccharification (temperature variables 55oCand 60oC).